Exponentiated Marshall-Olkin Exponential Distribution: Application of COVID-19 Second Wave in Nepal - Tharu, Ramesh Prasad; Pahari, Sakar; Sedhai, Gopal Prasad; Dhungana, Govinda Prasad (Nepal Journal of Mathematical Sciences, 2021)
available with pdf.